Naming, Shaming, Presupposing and Hypothesising in Farooq Kperogi’s Selected Essays - Evuti, Abdullahi Umar; Ogungbe, Ebenezer Oluseun; Usman, Mohammed Alhaji (NIU Journal of Humanities, 2026)
This study critically explores the stylistic elements in the socio-political writings of Farooq Kperogi. It focuses on how his linguistic and stylistic strategies construct and convey ideological critiques of governance, corruption, and social inequality in Nigeria. Employing a qualitative research approach, the study analyses a purposively selected corpus of ten essays published between 2019 and 2024, using critical stylistics as framework to examine features such as naming, presupposition, and negation. The findings reveal that Kperogi’s writings are characterised by evocative naming and shaming strategies, ideologically loaded presuppositions, and the strategic use of negation to emphasise governance failures and expose systemic corruption. His essays consistently situate these critiques within Nigeria’s socio-political discourse, highlighting issues such as nepotism, media complicity, political corruption, government laxity, and the erosion of democratic principles. The study concludes that Kperogi’s linguistic choices are not merely descriptive but perform a critical function, shaping public discourse and challenging dominant narratives. Kperogi engages readers in a way that fosters critical reflection and advocacy for accountability. Keywords: Critical Stylistics, Socio-Political Discourse, Farooq Kperogi, Linguistic Strategies, Nigeria, Governance Critique.